1991
DOI: 10.1111/j.1476-5381.1991.tb12473.x
|View full text |Cite
|
Sign up to set email alerts
|

BAY u3405, a potent and selective thromboxane A2 receptor antagonist on airway smooth muscle in vitro

Abstract: 1 BAY u3405 (3(R)- [[(4-fluorophenyl) sulphonyl]amino]-1,2,3,4-tetrahydro-9H-carbazole-9-propanoic acid) has been evaluated on airway smooth muscle, from a number of species including man, for its thromboxane A2 (TXA2) antagonist activity. 2 BAY u3405 was a potent, and competitive, antagonist of the TXA2-mimetic U46619-induced contractions of human, guinea-pig, rat and ferret airway smooth muscle with pA2 values between 8.0 and 8.9 and with no inherent contractile activity (10 -IO-M). 3 The TXA2 antagonist ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…Ramatroban was developed initially as a potent TP receptor antagonist (20). Recent studies revealed that this drug is also a CRTH2 antagonist and capable of inhibiting CRTH2-mediated eosinophil migration (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramatroban was developed initially as a potent TP receptor antagonist (20). Recent studies revealed that this drug is also a CRTH2 antagonist and capable of inhibiting CRTH2-mediated eosinophil migration (21).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PGD 2 alone elicited the production of IL-4, IL-5, and IL-13 by Th2 cells without affecting the production of IL-10. Ramatroban (BAY u 3405), original defined as a thromboxane-like prostanoid receptor (TP) antagonist and recently identified to also be a potent CRTH2 antagonist (20,21), abolished Th2 cell responses to PGD 2 . This inhibition was mediated by CRTH2 because SQ29548, a specific TP antagonist, did not mimic the effect of ramatroban.…”
Section: Ytokine Production From Cd4mentioning
confidence: 99%
“…Although the limited activity of GR 32191 may simply reflect low potency, it might alternatively reflect limited activity against all TXA2 receptor subtypes. McKenniff et al (1988McKenniff et al ( , 1991 have suggested that subtypes of TXA2 receptors exist in airway smooth muscle. They have demonstrated that some TXA2 antagonists, including GR 32191, were not equipotent at all such subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that high antagonist potency at all TXA2 subtypes is essential for a drug to clarify the role of TXA2 and PGD2 in asthma. It is probable that BAY u3405 is such a drug as it has been shown to have good activity at all TXA2 receptor subtypes (McKenniff et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation